2015
DOI: 10.1080/00981389.2015.1070780
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors of Self and Surrogate Online Health Information Seeking in Family Caregivers to Cancer Survivors

Abstract: The purpose of this research is to investigate various factors predicting online health information seeking for themselves (self OHIS) and online health information seeking for others (surrogate OHIS) in family caregivers to cancer survivors. To address this purpose, this study applies the comprehensive model of information seeking as a theoretical framework for explaining the relationships between various predictors and two types of OHIS. The data used in this study were taken from the Health Information Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 34 publications
1
31
0
2
Order By: Relevance
“…This integrative review by Park et al [ 13 ] included studies that do not differentiate between self-seeking and proxy seeking. Research has shown significant differences in characteristics of self-seekers and proxy seekers [ 7 - 9 , 16 ]. OHIS for oneself is typically based on different motives, needs, and circumstances than searching for someone else [ 8 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This integrative review by Park et al [ 13 ] included studies that do not differentiate between self-seeking and proxy seeking. Research has shown significant differences in characteristics of self-seekers and proxy seekers [ 7 - 9 , 16 ]. OHIS for oneself is typically based on different motives, needs, and circumstances than searching for someone else [ 8 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These scholars have investigated the relationship between and the effect of demographic characteristic variables, cognitive factors, internal factors, external factors, and OHISB. Specifically, based on a comprehensive model of information seeking, the older the family caregivers are, the less likely they are to conduct OHISB [10]. Several studies argued that self-efficacy is positively associated with OHISB [2,8,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Family members may also have selected information they assumed to be relevant or sought informational or emotional support only for themselves. Thus, information seeking by family members and friends is not always motivated by supportive intentions for the patient but may also be triggered by personal needs or by a mix of both . Further research is needed to understand the nature of the information exchange between surrogate seekers and patients (eg, whether and which information is passed on to the patient) and the motives of family members for contacting CISs.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the literature, surrogate‐information seeking is quite common . Several studies have presented data on family members and friends who seek health information on behalf of a cancer patient on the Internet or from a CIS . These studies indicated that surrogate seekers represented a distinct demographic group when compared with cancer patients seeking information for themselves .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation